Adaptive reuse of historical buildings and local residents’ actual visitation / Adlin Baizura Ariffin…[et al.] - Mohd Zahari, Mohd Salehuddin; Mohd Radzi, Salleh; Kutut, Mohd Zain (Faculty of Hotel and Management, Universiti Teknologi MARA, Selangor, Kampus Puncak Alam Campus, 2017)
Heritage tourism is one of the fastest growing components of tourism due to its ability to attract millions of international tourists and contribute billions of dollars to the host country. There are numbers of studies looking at the heritage tourism, mainly focusing on motivation, visitation behaviour, perceptions, appreciation, awareness and sustainability based on the public and architectural perspective. However, there is still lack of study looking at the influence of adaptive reuse of historical buildings toward the local resident’s actual visitation. Thus, to understand the phenomenon and filling the study gaps, this research note reviews the literatures, uplifting the issues in the proposed study contextual setting and developing the framework.